Desain Sistem Kendali Kecepatan Motor Induksi Pada Cane-Carier Based on Cohen-Coon Method - Adi Mulyadi (ZETROEM, 2021)
Abstract – This paper deal with the design of a 3-phaseinduction motor speed control system. The problem was the 3-phase induction motor speed does not maintain constant speed,an overshoot and a long rise time. The PID controller and a PIDtuning based on Cohen Coon are proposed to overcome constantspeed, overshoot and rise time. The simulation result shows thatthe uncontrolled speed of induction motor has an overshoot55.46%, rise time 17.72 ms, and peak amplitude 152 sec. Then, themotor speed by using PID controller has an overshoot 63.11%,rise time 13.75 ms, and peak amplitude is 100.8 sec. While themotor speed using the PID tuning based on Cohen Coon has anovershoot 53.11%, rise time 13.79 ms, and peak amplitude is 93.63sec. PID tuning based on Cohen Coon method can reduce moreovershoot 10%, more quickly rise time 0.04, and it can maintainthe motor speed at any condition.